Electrospinning and emerging healthcare and medicine possibilities - Liu, Ziqian; Ramakrishna, Seeram; Liu, Xiaoling (APL Bioengineering, 2020)
Electrospinning forms fibers from either an electrically charged polymer solution or polymer melt. Over the past decades, it has become a simple and versatile method for nanofiber production. Hence, it has been explored in many different applications. Commonly used electrospinning assembles fibers from polymer solutions in various solvents, known as solution electrospinning, while melt and near-field electrospinning techniques enhance the versatility of electrospinning. Adaption of additive manufacturing strategy to electrospinning permits precise fiber deposition and predefining pattern construction. This manuscript critically presents the potential of electrospun nanofibers in healthcare applications. Research community drew impetus from the similarity of electrospun nanofibers to the morphology and mechanical properties of fibrous extracellular matrices (ECM) of natural human tissues. Electrospun nanofibrous scaffolds act as ECM analogs for specific tissue cells, stem cells, and tumor cells to realize tissue regeneration, stem cell differentiation, and in vitro tumor model construction. The large surface-to-volume ratio of electrospun nanofibers offers a considerable number of bioactive agents binding sites, which makes it a promising candidate for a number of biomedical applications. The applications of electrospinning in regenerative medicine, tissue engineering, controlled drug delivery, biosensors, and cancer diagnosis are elaborated. Electrospun nanofiber incorporations in medical device coating, in vitro 3D cancer model, and filtration membrane are also discussed.